A new tremulane sesquiterpene from Irpex lacteus by solid-state fermentation. Issue 3 (1st February 2022) - Sun, Cheng-Tong; Wang, Jia-Peng; Shu, Yan; Cai, Xue-Yun; Hu, Jun-Tao; Zhang, Sheng-Qi; Cai, Le; Ding, Zhong-Tao
Abstract: A new tremulane sesquiterpene, lactedine (1 ), along with seven known tremulane sesquiterpenes (2 –8 ) and one known triterpene (9 ) were isolated from the fungus Irpex lacteus . Their structures were established on the basis of extensive spectroscopic data and DP4+ probability analyses. Graphical Abstract: